Unequal citizenship: what difference can the enfranchisement of women make? A case study of Kuwait. - Alsabeehg, Zeineb (Journal of Ethnic & Migration Studies)
Today, unequal citizenship is prevalent in women's unequal ability to confer citizenship on their children in 24 countries – including Kuwait. Historical and contemporary country cases suggest that democratisation and the introduction of universal suffrage do not necessarily entail equality reforms in citizenship law. This article examines whether equipping women with political rights nevertheless makes a difference in their struggles for equal citizenship rights. By studying Kuwait as a case study, which introduced female suffrage in 2005 while still restricting women's ability to confer citizenship on their children to this day, this article highlights three ways in which electoral rights are instrumentalised to claim equal citizenship. First, women run for office and, when elected, raise issues in the parliament that can bring about equality. Second, women vote for candidates who support their cause. Third, women deliberately choose to abstain from voting in protest if they feel neglected by lawmakers. Furthermore, this article looks at Kuwait's episode of electoral backsliding since May 2024, when the emir ruled to temporarily dissolve the parliament and suspend elections, to emphasise that when (female) citizens had access to electoral rights, they used them in their struggles for equal citizenship.